Las bibliotecas escolares en el currículum universitario: análisis de su situación y necesidades - Balça, Ângela (2012)
School libraries are more and more important in educational system. Well provided, managed and integrated school libraries have many benefits, not only over the student – as they improve their achievement, but also over the teachers and the whole educational community. It’s necessary the future teachers to learn how to work with, and within them, and how to integrate them in their teaching. That’s why we need to know university students in teaching degrees’ pre-conceptions, in order to fix curricula to correct their prejudices or fill their shortages. To that end, we collected, by means of surveys, the conceptions and opinions about school libraries of the students from two population samples of future teachers of elementary education: a Spanish one – students of “Educación Infantil” and “Educación Primaria” from Universidad de Extremadura; and a Portuguese one – students of “Educação Basica”, “Educação de Infancia” and “Professor de Primaria” from Universidade de Évora. We choose that type of populations because teachers of elementary education have a major role in promotion of reading for children, they bring up new readers. We analysed their answers, finding some relevant concepts and shortages in their pre-conceptions about school libraries, like their lack of knowledge about regulations or their ignorance about how to integrate the school library in their lessons with children. These results can and should be examined and studied, and therefore used for improving knowledge and competences in university curricula in teaching degrees, about such important subject.